THE SOLUTION OF A MATHEMATICAL MODEL FOR COVID-19 TRANSMISSION AND VACCINATION IN NIGERIA BY USING A DIFFERENTIAL TRANSFORMATION METHOD (FUDMA JOURNAL OF SCIENCES, 2022)
In this work, Differential Transform Method (DTM) was employed to obtain the series solution of the SIRV COVID-19 model in Nigeria. The validity of the DTM in solving the model was validated by Maple 21’s Classical fourth-order Runge-Kutta method. The comparison between DTM and Runge- Kutta (RK4) solutions was performed and there was a good correlation between the results obtained by the two methods. The result validates the accuracy and efficiency of the DTM to solve the model
Keywords: SIRV, DTM, Runge Kutta, Covid-19, Maple, Nigeria